Does policy analysis matter? : exploring its effectiveness in theory and practice - Friedman, Lee S.; Friedman, Lee S. (Aaron Wildavsky forum for public policy ;, 2017)
"This book is about the effort to improve governmental policy-making through the development, beginning in the 1950s, of a new profession of advisors and public managers trained in public policy analysis and strategic public management. The use of such professionals has become commonplace at all levels of government within the United States and in many other countries around the world. A central question that we examine is this: what have we learned about the effects of this new profession on public policies and on policy making? Does policy analysis matter? Closely related to this central question is another one: does what we have learned offer lessons for whether and how policy analysis can be improved? Each of the essays in this book is designed to make us think better and harder about how to improve the practice and use of policy analysis. We consider what we have learned so far about whether and how policy analysis matters, how this learning helps to generate ideas for improving practice, and why learning more about this is an important agenda for future research"--Provided by publisher